KLINIČKI SINDROMI POREMEĆAJA IZ SPEKTRA PSIHOZA I NJIHOVA POVEZANOST SA KVALITETOM ŽIVOTA TOKOM OPORAVKA - Marić, Nađa (Medical Research, 2022)
Introduction/Aim: Quality of life (QoL) as a measure of subjective well-being is an important indicator in the everyday functioning of patients with psychosis spectrum disorders (PSD). The aim of this study was to explore the association between QoL and five symptom domains in outpatients with PSD. Our hypothesis was that negative and affective symptom domains would be associated with lower QoL. Materials and methods: Socio-demographic and clinical data were collected from 68 participants who met the prerequisite for the current study – adult outpatients diagnosed with F20.x-29 (according to ICD-10), qualified by the attending physicians as stable. Symptoms were assessed using the expanded version of the Brief Psychiatric Rating Scale (BPRS-E) on the basis of which five symptom domains were quantified: positive symptoms, negative symptoms, affective symptoms (anxiety/depression), activation and disorganization. QoL was measured with the ten-pointRecovering Quality of Life (ReQol) scale. Results: Mean age (SD) of the sample was 43.3 (11.0) years, and 60.3% of participants were male. ReQoL mean (SD) score was 25.4 (8.4) and BPRS-E mean total score was 1.9 (0.5). Regarding the BPRS-E and QoL scores differences between males and females, educational level or marital status were not observed. Linear regression analyses showed that two out ot five symptom domains were significantly associated with ReQoL: Affective domain (β coeff.=-.717, p<.001) and negative symptom domain (β coeff.=-.299, p=.001). Conclusion: The present study of real-world clinically stable patients with PSD demonstrated that affective symptoms (depression/anxiety) had the strongest negative association with QoL in comparison to other symptom domains. This information could be useful for clinicians who should try to alleviate distress in order to improve the PSD treatment outcome.